(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
There are many great teachers who have faithfully served their country at any time and carried out educational activities, leaving behind the archives of the history of the nation and the ancient Kazakh culture. Among them is Ahmet Baitursynov, who carried the burden of a century worth of special mention, who in the turmoil of his time gave the young generation a spring of knowledge and education. He is a perfect writer, whose walls are broken for the Kazakh people, who grieves for their future, who calls the whole society to a breakthrough and wake them up.